Pengembangan Butik Muslim yang Terkait dengan Pelayanan Prima dan Kualitas Produk pada Butik Firta Collection - Esust Setiawati (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2018)
This study aims to analyze how strategic management in the Firta Collection Boutique to develop its business, especially in providing services to customers. The method used in this research is a qualitative method that includes Marketing Mix (4P Analysis) and SWOT Analysis, to find out what external factors are opportunities or threats to the Firta Collection Boutique. The results of the study show that the strategies adopted by the Firta Collection Boutique are still inappropriate and need to use other strategies. Changes in the external environment have continued to increase so that it is an opportunity and anticipates threats by utilizing strengths and minimizing weaknesses by innovating and improving approaches and gaining customer trust in product quality, in order to compete in the fashion sector.